Measurement-Based Models of Delivery and Interference in Static Wireless Networks - Reis, Charles; Mahajan, Ratul; Rodrig, Maya; Wetherall, David; Zahorjan, John (SIGCOMM, 2006)
We present practical models for the physical layer behaviors of packet reception and carrier sense with interference in static wireless networks. These models use measurements of a real network rather than abstract RF propagation models as the basis for accuracy in complex environments. Seeding our models requires trials in an N node network, in which each sender transmits in turn and receivers measure RSSI values and packet counts, both of which are easily obtainable. The models then predict packet delivery and throughput in the same network for different sets of transmitters with the same node placements. We evaluate our models for the base case of two senders that broadcast packets simultaneously. We ﬁnd that they are effective at predicting when there will be signiﬁcant interference effects. Across many predictions, we obtain an RMS error for 802.11a and 802.11b of a half and a third, respectively, of a measurement-based model that ignores interference.